Chapter 6 Digital Editing and the Greek New Testament - Houghton, H. A. G. (Digital Biblical Studies, 2016)
The textual tradition of the Bible has inspired many of the most significant developments, principles and methodologies in editorial practice, from the parallel texts and critical symbols of Origen's Hexapla in the early third century to Lachmann's nineteeth-century stemmatics. It is therefore unsurprising that, in this digital age, the New Testament continues to be at the forefront of new and exciting initiatives. The present chapter describes the workflow and tools developed for the Editio Critica Maior of the Greek New Testament, in particular those associated with the Workspace for Collaborative Editing, and how these have shaped the task of editing both the text and documents of the New Testament and offer new models of publication thanks to the capacity of electronic media and the Internet.